2011
DOI: 10.1155/2011/847831
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve in a Western Training Center of the Circumferential En Bloc Esophageal Endoscopic Submucosal Dissection in an In Vivo Animal Model

Abstract: Aim. Evaluate the feasibility to overcome the learning curve in a western training center of the en bloc circumferential esophageal (ECE-) ESD in an in vivo animal model. Methods. ECE-ESD was performed on ten canine models under general anesthesia on artificial lesions at the esophagus marked with coagulation points. After the ESD each canine model was euthanized and surgical resection of the esophagus and stomach was carried out according to “the Principles of Humane Experimental Technique, Russel and Burch.”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…An endoscopist with previous training in an important endoscopy teaching center in Japan performed gastric ESDs in mongrel dogs that weighed 18 to 20 kg, either with a Hook knife or an IT-knife, successfully, and without any complications. The same group proved the feasibility of a similar canine model to train in circumferential esophageal ESD 23. Moreover, a learning curve was proven, as perforations occurred in the initial seven cases, whereas the last three cases were completed uneventfully.…”
Section: Evidence About Animal Models For Training In Esdmentioning
confidence: 75%
“…An endoscopist with previous training in an important endoscopy teaching center in Japan performed gastric ESDs in mongrel dogs that weighed 18 to 20 kg, either with a Hook knife or an IT-knife, successfully, and without any complications. The same group proved the feasibility of a similar canine model to train in circumferential esophageal ESD 23. Moreover, a learning curve was proven, as perforations occurred in the initial seven cases, whereas the last three cases were completed uneventfully.…”
Section: Evidence About Animal Models For Training In Esdmentioning
confidence: 75%
“…Thus, the necessity of specific training before embarking on the procedure in humans is evident. It has been reported that training for esophageal ESD in an anesthetized live pig is a valuable option [26][27][28]. However, the number of institutions that can offer training using live pigs is limited because their use requires expensive instrument and special facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports clarified the usefulness of a live animal model for learning ESD [26][27][28]. However, live animal models are expensive and not all institutions or hospitals are equipped for their usage.…”
Section: Introductionmentioning
confidence: 99%
“…However, ESD is time consuming and associated with a higher rate of adverse events, such as perforation, bleeding, and esophageal stricture [3,8,9,18]. The ESD procedure is laborious and requires a high level of skill, and acquiring the ability to perform ESD involves a slow learning curve [19]. The incidence of procedure-related adverse events is highly dependent on operator proficiency.…”
Section: Discussionmentioning
confidence: 99%